Development of statistical models for trihalomethane (THM) occurrence in a water distribution network in Central Thailand - Manunart Feungpean (2018)
© 2014, © 2014 Taylor & Francis. This study initially investigated the occurrence of trihalomethanes (THMs) in the water supply system of Metropolitan Bangkok, Thailand, evaluating 624 samples collected between 2007 and 2009. It was found that the mean total THM concentration was 66 μg/L, with CHCl3 accounting for 85% of the total. The main focus, however, was the development of models using linear and non-linear regression analyses to determine the effect of key disinfection parameters on THM formation. Regression techniques revealed that the total and residual Cl2 concentrations, and contact time (expressed as the equivalent pipe distance) played the most critical role in THM formation, regardless of the season investigated. A moderate correlation was generally observed, however, the correlation was considerably stronger in the dry seasons (i.e. winter and summer) compared to the rainy season. Furthermore, the similarity in statistical parameters regarding the actual and predicted THM concentrations suggests that the models developed are reliable.